(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Natal tooth are the teeth which can be present at birth whereas neonatal tooth appears within 30 days after birth which is an unusual and rare situation. The exact etiology behind this is unknown and various factors may be related to these teeth. Both natal and neonatal teeth are notably important for pediatric dentists and pediatricians. This case report describes the management of 24 days old infant with a mobile mandibular natal tooth related to Rigafede disease. After 45 days, there’s a recurrence of early infancy tooth followed by extraction of natal tooth.